1990
DOI: 10.2135/cropsci1990.0011183x003000060014x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses and Mineral Nutrient Relations of Salt‐Stressed Sorghum

Abstract: The production of sorghum [Sorghum bicolor (L.) Moench], a moderately salt‐tolerant crop, often occurs in areas of relatively low rainfall and on marginal soils containing excess salts. Despite the importance of sorghum to agriculture, relatively less is known about its response to these stressful environments than that of other major cereal grain crops. The purpose of this investigation was to study the effects of moderate levels of salinity on growth, assimilate partitioning, and mineral nutrient relations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 0 publications
4
34
1
7
Order By: Relevance
“…It also reflects salt impact on tissues, reduction in photosynthetic rates per unit of leaf area (Netondo et al, 2004), and attainment of maximum salt concentration tolerated by the fully expanded leaves (Munns et al, 2006). These findings agree with those from sorghum (Boursier and Läuchli, 1990 , the plants could not regulate ion concentration, since there may have been severe physiological dysfunctions leading to decreased growth rates and eventually cell death leading to death of whole plant. Shoot and root damages caused by ion toxicity, osmotic effects or both may have contributed to the observed sharp drop in dry weights preceding the death of highly-stressed plants.…”
Section: Discussionsupporting
confidence: 54%
“…It also reflects salt impact on tissues, reduction in photosynthetic rates per unit of leaf area (Netondo et al, 2004), and attainment of maximum salt concentration tolerated by the fully expanded leaves (Munns et al, 2006). These findings agree with those from sorghum (Boursier and Läuchli, 1990 , the plants could not regulate ion concentration, since there may have been severe physiological dysfunctions leading to decreased growth rates and eventually cell death leading to death of whole plant. Shoot and root damages caused by ion toxicity, osmotic effects or both may have contributed to the observed sharp drop in dry weights preceding the death of highly-stressed plants.…”
Section: Discussionsupporting
confidence: 54%
“…The analysis of the correlations between root organic solutes versus RGR and NAR showed that as the root organic solute contents increase the plants tend to be more salt-tolerant. Under salt stress, the salt-sensitive genotype showed the lowest root Na + content, which could be explained by the lower capacity of the plants to retain sodium in their root cells when they were grown under such conditions (Greenway and Munns, 1980;Boursier and Läuchli, 1990). In addition, the salt-induced depletion of the root soluble organic solute contents in this genotype may be due to the inhibition of net photosynthesis (figure 1), reducing the amount of carbon fixed in the shoot and transported to the roots (Richardson and McCree, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Among the many mechanisms of salinity tolerance (Munns & Tester, 2008), the ability to restrict the entry of saline ions through the roots and limit the transport of Na + and/or Cl -to aerial parts, retaining these ions in the root and lower stem, has to be one of the most important of all the traits associated with tolerance (Colmer et al, 2005;Maathuis & Amtmann, 1999;Murillo-Amador et al, 2006). A related trait, the retention of toxic ion in roots, has been proposed to be important to salt tolerance in plants (Boursier & Läuchli, 1990;Pérez-Alfocea et al, 2000). Species that keep acceptable growth rates and possess mechanisms to exclude Na + and Cl -from roots or leaves and still have good appearance are ideal for landscaping.…”
Section: Mechanisms Of Tolerancementioning
confidence: 99%